2016
DOI: 10.1111/asj.12629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aloe vera and synbiotic as antibiotic growth promoter substitutions on performance, gut morphology, immune responses and blood constitutes of broiler chickens

Abstract: This study was performed to investigate the effect of dietary supplementation with Aloe vera (AV) powder and synbiotic as growth promoter agents on performance, gut morphology, immune responses, hematology and serum biochemistry in broilers. A total of 240-day-old male broiler chicks (Ross 308) were randomly assigned to six treatments with four replicates. Birds were offered either a corn-soybean meal basal diet (control) or the basal diet supplemented with 200 mg/kg virginiamycin (VM), 1 g/kg synbiotic (Syn),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
(83 reference statements)
4
23
0
Order By: Relevance
“…Additionally, Awad et al . and Naghi Shokri et al . also found that the inclusion of synbiotics increased the villus:crypt ratio in the intestine of broilers.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, Awad et al . and Naghi Shokri et al . also found that the inclusion of synbiotics increased the villus:crypt ratio in the intestine of broilers.…”
Section: Discussionmentioning
confidence: 93%
“…Detailed procedures about intestinal morphology detection were based on a previous description (Naghi Shokri et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Villus height, crypt depth and wall thickness were determined using a phase contrast microscope. Detailed procedures about intestinal morphology detection were based on a previous description (Naghi Shokri et al 2016).…”
Section: Intestinal Morphologymentioning
confidence: 99%
“…Synbiotics would beneficially affect the host by improving the survival and persistence of living microbial dietary supplements in the gastrointestinal tract, as well as by selectively stimulating the growth and/or activating the metabolism of one or a limited number of health‐promoting bacteria . In broiler chickens, previous in vivo studies have shown that dietary supplementation with various synbiotics can promote growth rate and feed utilization efficiency, replace antibiotics, stimulate the proliferation of beneficial bacteria but inhibit the colonization of pathogenic bacteria, regulate the immune system, maintain intestinal integrity, and improve the circulating redox homeostasis and nutrient absorption . Additionally, in ovo ‐delivered synbiotics can modulate the central and peripheral lymphatic organ development in broiler chickens .…”
Section: Introductionmentioning
confidence: 99%